Enhancing undergraduate research talents: the role of tutors in dental basic research education - Miao, Xiaoyu; Chen, Xuanyu; Li, Jiayi; Wu, Zhe; Guo, Lvhua; Luo, Siqi; Luo, Tao; Yang, Xuesong (Frontiers in Medicine, 2024)
Purpose: This study endeavors to investigate ways to optimize the role of teachers in undergraduate dental basic research education (UDBRE) with the aim of nurturing the research potential of undergraduate students.: We conducted a cross-sectional study among medical undergraduates enrolled at the School of Stomatology, Guangzhou Medical University. Descriptive statistics were employed to comprehensively analyze UDBRE's fundamental aspects. Kendall rank correlation analysis was performed to evaluate the relationship between the quality of feedback provided by tutors to undergraduates and the students' scientific research abilities. Additionally, multivariate logistic regression analysis was employed to uncover the factors influencing the effectiveness of UDBRE. Results: A total of 168 medical students were surveyed with a valid response rate of 93.85%. The effectiveness of UDBRE was demonstrated by undergraduates' self-rated research abilities, active participation in scientific research projects, and a certain amount of academic outputs. Significant and positive correlations (𝓣b>0.5, P<0.001) were identified between the tutor-undergraduate feedback quality and students' self-rated scores for scientific research abilities. These abilities included developing scientific questions, designing research projects, retrieving and reading literature, academic writing, experiment operation, and analyzing and evaluating experimental results. Positive effects on students' academic performance (P<0.05) were observed when higher-quality feedback, an authoritative tutoring style and tutors with middle-career experience were present. Conclusions: This study underscores the pivotal role of UDBRE in fostering the scientific research aptitude of medical undergraduates. It emphasizes the constructive influence of tutor-undergraduate feedback, authoritative teaching styles, providing valuable insights for establishing an effective mentorship framework.